ASSOCIATION OF VITAMIN D DEFICIENCY WITH FEMALE INFERTILITY AND IVF OUTCOMES - Nabaa shakir Mahmood; Amna Lootah; Sohyla Abdalla; Anas Emad Ali Masoud; Sham Bassem Abou Al Fadel; Mafaz Al Khaffaf; Israa Fouad Elsayed Farag Hussein; Sara Ahmed Al Amoodi; Samaha Kanden Mohammed Shafi; Ashmita Josephine Pinheiro (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Vitamin D is a fat-soluble vitamin that is indispensable for the proper functioning of the human body due to its ability to influence the processes of calcium-phosphate metabolism, immune response, and cell differentiation. It has been suggested that it harms female fertility and IVF success rate with ovarian function, hormonal changes, and receptivity of endometrium. Therefore, Vitamin D deficiency and its relationship with infertility, especially among women seeking fertility treatment through IVF, has remained inconclusive. Purpose of the meta-analysis: Here, the writer intends to estimate the association between Vitamin D deficiency and female infertility, particularly with IVF implantation rates, pregnancy, live birth rates, and miscarriage rates. A literature search was performed using databases including PubMed, Scopus, and Web of Science with regards to “Vitamin D deficiency,” “female infertility,” “IVF outcomes,” and “fertility treatment.” In this review, a quantitative analysis was done for the eligible populations from specified study types of research studies such as randomized controlled trials, cohorts, and case-control trials. It specified the types of measurements of Vitamin D, the number of participants, and IVF outcomes. The source of evidence populated in the meta-analysis encompasses studies in different populations, and what was identified was the fact that Vitamin D deficiency is a critical factor in poor IVF outcomes, including implantation, pregnancy, and miscarriage rates. The findings noted that the adverse effects were significantly more pronounced among the women with higher BMI and older age. Also, there was a variation in Vitamin D metabolism among the ethnic groups, with women belonging to certain groups classified as possibly Vitamin D deficient. In light of the matters stated above, this systematic review indicates that Vitamin D deficiency plays a part in female infertility and decreased chances of IVF. This literature supports the recommendations for vitamin D supplementation to enhance the success of IVF but calls for more high-quality randomized controlled trials to follow up on the subject and set definite protocols for supplementation.